Other Americans : the art of Latin America in the US imaginary - Bush, Matthew, 1976- (Illuminations (Pittsburgh, Pa.), 2022)
"Grounded in perspectives of affect theory, Other Americans examines the writings of Roberto Bolaño and Daniel Alarcón; films by Alfonso Cuarón, Claudia Llosa, Matt Piedmont, and Joel and Ethan Coen; as well as the Netflix serials Narcos and El marginal. These widely consumed works about Latin America--equally balanced between narratives produced in the United States and in the region itself--are laden with fear, anxiety, and shame, which has an impact that exceeds the experience of reception. The negative feelings encoded in visions of Latin America become common coinage for US audiences, shaping their ideological relationship with the region and performing an affective interpellation. By analyzing the underlying melodramatic structures of these works that would portray Latin America as an implicit other, Bush examines a process of affective comprehension that foments an us/them, or north/south binary in the reception of Latin America's globalized art"--